1995
DOI: 10.1016/s1071-3581(05)80077-7
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of uptake of technetium-tetrofosmin. II: Uptake into isolated adult rat heart mitochondria

Abstract: It was concluded that the accumulation of 99mTc-labeled tetrofosmin by the mitochondria is related to their ability to transduce metabolic energy into electronegative membrane potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(54 citation statements)
references
References 13 publications
1
53
0
Order By: Relevance
“…This is strikingly similar to the known mechanism of cationic [ 99m Tc]sestamibi and [ 99m Tc] tetrofosmin accumulation and retention based on the potential gradient sustained in viable mitochondria. [30][31][32] The high concentration of mitochondria in the heart tissue provides a reservoir for the flow tracers.…”
Section: Discussionmentioning
confidence: 99%
“…This is strikingly similar to the known mechanism of cationic [ 99m Tc]sestamibi and [ 99m Tc] tetrofosmin accumulation and retention based on the potential gradient sustained in viable mitochondria. [30][31][32] The high concentration of mitochondria in the heart tissue provides a reservoir for the flow tracers.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] In patients with AMI who underwent reperfusion therapy, the RR phenomenon has been demonstrated on 99m Tc-labeled flow tracers myocardial scintigraphy and the myocardium that shows the RR phenomenon of 99m Tc-labeled flow tracers is thought to be damaged, though contractile function is preserved to a certain extent. [7][8][9] Sugihara et al 7 reported that the impairment of the LV wall motion in the regions showing the 99m Tc-tetrofosmin RR phenomenon, evaluated using contrast left ventriculography, ranged from akinesis/dyskinesis to normal, but was significantly better than that in the regions with a fixed defect.…”
Section: Reverse Redistribution Phenomenon Of 99m Tc-tetrofosminmentioning
confidence: 99%
“…26,27 Kresnik et al 8 reported decreased tetrofosmin uptake in patients with degenerative goiter and HT in a late scan obtained at 1 h after injection. In other study, Younes et al 25 showed that the mechanism of tetrofosmin uptake was dependent on the amount of mitochondrial proteins using cell-based systems. Based on the data from Younes's report, 25 Kresnik et al 8 suggested that the decrease or loss of uptake capability in thyroid tissue was due to degenerative changes.…”
Section: Fi Gu Rementioning
confidence: 98%
“…Thus, we suggest that the changes in 99m Tc-tetrofosmin kinetics in thyroid tissue parallels the degree of thyrocyte destruction in HT. Tetrofosmin is a perfusion agent, 25 and is an indicator of cell viability. 26,27 Kresnik et al 8 reported decreased tetrofosmin uptake in patients with degenerative goiter and HT in a late scan obtained at 1 h after injection.…”
Section: Fi Gu Rementioning
confidence: 99%